2021
DOI: 10.2147/oaem.s289748
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Predictors of Abnormal Calcium, Magnesium and Phosphorus Blood Levels in the Emergency Department: A Retrospective Cohort Study

Abstract: Purpose: With rising healthcare costs limiting access to care, the judicious use of diagnostic tests has become a critical issue for many jurisdictions. Calcium, magnesium and phosphorus serum levels are regularly performed tests in the emergency department, but their clinical relevance have come into question. Authors sought to determine risk factors that could predict abnormal calcium, magnesium and phosphorus serum levels, as well as identify patients who may need corrective interventions. Methods: A retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Among ED patients, the 6.9% incidence of hypo-iMg is lower than in the literature. An Australian study showed a 10% of abnormal (hypo and hyper) serum Mg level [ 39 ] and a recent study based on 1008 patients found a 17.2% rate of hypomagnesemia [ 40 ]. When using the ranges determined in our study, the 9.2% incidence of hypo-iMg seems more relevant especially since it is significantly higher than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Among ED patients, the 6.9% incidence of hypo-iMg is lower than in the literature. An Australian study showed a 10% of abnormal (hypo and hyper) serum Mg level [ 39 ] and a recent study based on 1008 patients found a 17.2% rate of hypomagnesemia [ 40 ]. When using the ranges determined in our study, the 9.2% incidence of hypo-iMg seems more relevant especially since it is significantly higher than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Variants of the TRPM6 gene-another TRP channel belonging to subfamily M, which is a close homolog of TRPM7 [31]-caused hypomagnesaemia accompanied by seizures [32]. Two recent studies did not find seizures as a significant risk factor for hypomagnesaemia [33,34], but seizures are among the neurological symptoms that may occur in those with severe hypomagnesaemia [35,36]. A meta-analysis of 40 studies showed that the serum magnesium concentrations were not different between epilepsy patients and control subjects, but hair magnesium concentrations were lower in both treated and non-treated patients compared to controls.…”
Section: Introductionmentioning
confidence: 99%